Association between nighttime sleep duration and cognitive function in middle-aged and older adult patients with multimorbidity: the mediating role of depression - Ming Jia; Xingyu Liu; Xiuwei Da (Frontiers in Public Health, 2025)
ObjectiveTo investigate the mediating role of depression in the relationship between nighttime sleep duration and cognitive function among middle-aged and older adult patients with multimorbidity, providing insights for mitigating cognitive decline.MethodsUtilizing data from the China Health and Retirement Longitudinal Study (CHARLS) (2015 and 2020 waves), 4,210 participants with ≥2 chronic conditions were included. Correlation, regression, and mediation analyses were conducted to examine associations between sleep duration, depression, and cognitive function.ResultsThe prevalence of cognitive impairment was 35.7%. Nighttime sleep duration showed a weak positive correlation with cognitive function (r = 0.071, p < 0.01) and a stronger negative correlation with depression (r = −0.251, p < 0.01). Depression was negatively correlated with cognitive function (r = −0.262, p < 0.01). Mediation analysis revealed that depression fully mediated the sleep-cognition relationship [indirect effect: 0.120, 95% CI (0.100–0.141); direct effect nonsignificant].ConclusionDepression fully mediates the association between nighttime sleep duration and cognitive function in multimorbidity patients. Interventions targeting sleep hygiene and mental health may synergistically alleviate cognitive decline in this population.